Relationship between Knowledge Level and Mother's Attitude to Basic Immunization for Infants 9-12 Months at North Jayapura Health Center - Nasrah Nasrah; Qoriah Nur; Blestina Maryorita; Rita Evalina Butar-Butar (Institute of Computer Science (IOCS), 2022)
This study aims to explain the relationship between knowledge level and mother's attitude towards basic immunization for infants 9-12 months at the Jayapura Utara Public Health Center. The design of this study used descriptive analytic by using a cross sectional approach. The population in this study were all mothers who had babies aged 9-12 months in the working area of the North Jayapura Health Center from a baby population of 157 people. The sampling technique in this study was carried out using purposive sampling or judgment sampling, the sample required was 75 mothers. The results of this study indicate that 1) The results of the bivariate analysis of the relationship between the mother's level of knowledge on basic immunization obtained a p value of 0.000 or p value < (0.05), which means that there is a relationship between the mother's level of knowledge on basic immunization in infants, and 2) The results of the bivariate analysis of the relationship between mother's attitude towards basic immunization obtained a p value of 0.014 or p value < (0.05), there was a relationship between mother's attitude towards basic immunization in infants.